Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Nine takeaways from our reviews of COVID-19 education responses - Chuang, Rachel; Kaye, Tom; Koomar, Saalim; McBurnie, Chris; Moss Coflan, Caitlin (EdTech Hub, 2020)
Regular readers will know about our Helpdesk, the on-demand support service we provide for FCDO advisers and World Bank staff to help them make evidence-informed decisions. Since the onset of coronavirus, the Helpdesk team has responded to requests from 15 countries across Africa, Asia, and the Middle…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The EdTech Hub’s Helpdesk and COVID-19: Demand-driven advice (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. With more than 1.5 billion children now affected by school closures, ministries of education and decision-makers around the world are urgently in need of fast, evidence-based, context-specific advice about out-of-school learning. Teachers, caregivers, parents and policymakers are tirelessly working to ensure that learning doesn’t stop. Faced with one of the…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH